2009
DOI: 10.2460/ajvr.70.8.1013
|View full text |Cite
|
Sign up to set email alerts
|

Identification of chromosomal regions associated with cranial cruciate ligament rupture in a population of Newfoundlands

Abstract: In the population of Newfoundlands, 4 MSATs that were located on 4 chromosomes were significantly associated with the CCLR trait. Three of those markers were validated in part via genotyping additional closely located markers. The MSATs that were associated with the CCLR trait were identified in all regions (except for those on chromosome 24). Newfoundlands with CCLR could be used to study the disease process associated with anterior cruciate ligament injuries that occur in young female human athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 13 publications
0
22
0
1
Order By: Relevance
“…However, the presence of stifle synovitis histologically increases the risk of subsequent contralateral CrCLR [10], although there is no evidence of a MHC class II immunogenetic association [38]. Non-contact CrCLR is a complex trait, with multiple genes contributing to development of the phenotype [39]. Heritability is estimated to be 0.27 in Newfoundlands, suggesting that extrinsic factors also have a substantial effect on expression of the phenotype [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the presence of stifle synovitis histologically increases the risk of subsequent contralateral CrCLR [10], although there is no evidence of a MHC class II immunogenetic association [38]. Non-contact CrCLR is a complex trait, with multiple genes contributing to development of the phenotype [39]. Heritability is estimated to be 0.27 in Newfoundlands, suggesting that extrinsic factors also have a substantial effect on expression of the phenotype [40].…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic factors include genetics, cruciate ligament matrix composition, stifle morphology, and body weight. Extrinsic factors include body condition, whether or not ovariohysterectomy or castration has been performed, and development of synovitis [4], [10], [39][45]. In the present study, we examined the effect of gender, breed, body weight, age, and TPA on risk of subsequent contralateral CrCLR in a large population of dogs.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported a prevalence for CCL deficiency of 22%, and proposed a recessive mode of inheritance, with 51% penetrance. Four microsatellite markers located on 4 chromosomes were consequently associated with CCL deficiency in a subset of 90 Newfoundlands 15 . In spite of the particularly high prevalence and OR in that breed, only 27% of the phenotypic expression of CCLD in these dogs was attributable to genetics, whereas 73% was linked to environmental factors 14 .…”
Section: Influence Of Geneticsmentioning
confidence: 98%
“…Four putative QTL were described that underlie RCCL in this Newfoundland pedigree [16]. A GWAS conducted on these same Newfoundland dogs reported associations on CFA1, 10, and 33 [21], none of which overlapped with the loci previously reported by linkage analysis in the same pedigree [22]. However, single nucleotide polymorphisms (SNPs) in key genes involved in ligament strength, stability and extracellular matrix composition were associated with RCCL susceptibility across a single case and a single control from four different dog breeds [21].…”
Section: Introductionmentioning
confidence: 95%